Cold-Hardiness of Cryptopygus antarcticus (Collembola) from Bouvetøya - Sømme, Lauritz (Oikos, 1978)
Cryptopygus antarcticus Willem were extracted from samples of mosses collected at Bouvetøya during the Norwegian Antarctic Expedition in February 1977. The body length of the collembolans from these samples ranged from 225 to 1125 μm. The collembolans had average supercooling points between -24° and -26°C. Acclimation at -5°, 0° and 12°C for various time intervals had no significant effect on their ability to supercool. Glycerol was not found in specimens acclimated at -5° and 0°C. All specimens were killed by freezing at temperatures in the range of their supercooling points. Chill-coma temperatures of the collembolans were between -2° and -7°C.
Keywords: Bouvetøya; NARE 1976/77; kuldetoleranse; leddyr; virvelløse dyr; zoologi